The Scientific Revolution Revisited - Teich, Mikuláš (Open Book Publishers, 2015)
"The Scientific Revolution Revisited brings Mikuláš Teich back to the great movement of thought and action that transformed European science and society in the seventeenth century. Drawing on a lifetime of scholarly experience in six penetrating chapters, Teich examines the ways of investigating and understanding nature that matured during the late Middle Ages and the Renaissance, charting their progress towards science as we now know it and insisting on the essential interpenetration of such inquiry with its changing social environment. The Scientific Revolution was marked by the global expansion of trade by European powers and by interstate rivalries for a stake in the developing world market, in which advanced medieval China, remarkably, did not participate. It is in the wake of these happenings, in Teich's original retelling, that the Thirty Years War and the Scientific Revolution emerge as products of and factors in an uneven transition in European and world history: from natural philosophy to modern science, feudalism to capitalism, the late medieval to the early modern period. With a narrative that moves from pre-classical thought to the European institutionalisation of science – and a scope that embraces figures both lionised and neglected, such as Nicole Oresme, Francis Bacon, Thomas Hobbes, Isaac Newton, René Descartes, Thaddeus Hagecius, Johann Joachim Becher – The Scientific Revolution Revisited illuminates the social and intellectual sea changes that shaped the modern world."